Cinema, democracy and perfectionism: Joshua Foa Dienstag in dialogue - Foa Dienstag, Joshua (Critical Powers, 2016)
In the lead essay for this volume, Joshua Foa Dienstag engages in a critical encounter with the work of Stanley Cavell on cinema, focusing sceptical attention on the claims made for the contribution of cinema to the ethical character of democratic life. In this debate, Dienstag mirrors the celebrated dialogue between Rousseau and Jean D'Alembert on theatre, casting Cavell as D'Alembert in his view that we can learn to become better citizens and better people by observing a staged representation of human life, with Dienstag arguing, after Rousseau, that this misunderstands the relationship between original and copy, even more so in the medium of film than in the medium of theatre. The argument is developed further by essays from Clare Woodford, Tracy B. Strong, Margaret Kohn, Davide Panagia and Thomas Dunn, to which Dienstag responds in the concluding chapter, 'A reply to my critics'.